Bottom-up analysis of energy conservation and carbon dioxide mitigation potentials by extended marginal abatement cost curves for pulp and paper industry. (July 2022) - Huang, Yun-Hsun; Wu, Jung-Hua; Liu, Tzu-Yi
Abstract: The energy-intensive pulp and paper industry is a major contributor to carbon dioxide emissions. The potential to reduce energy consumption and carbon dioxide emissions is generally assessed using energy conservation supply curves and marginal abatement cost curves; however, both of these methods have inherent faults. For a given negative cost, conventional marginal abatement cost curves tend to favor options that lead to small reductions in carbon dioxide emissions over options that produce larger reductions. In the current study, we employed extended versions of energy conservation supply curves and marginal abatement cost curves to analyze the various options to reduce energy consumption and carbon dioxide emissions. The technical potential energy savings and carbon dioxide abatement were respectively estimated at 5.05% of the final energy use in the sector and 6.32% of carbon dioxide emissions in 2019. We determined that 52.3% of the electricity savings and 82.8% of fuel savings could be achieved in a cost-effective manner. Additionally, the utilization of solid recovered fuels remains a largely untapped opportunity to reduce carbon dioxide emissions for the Taiwanese pulp and paper industry. Thus, efforts should be made to establish a comprehensive database pertaining to the direction and volume of waste flows and improve waste collection networks with corresponding standards pertaining to solid recovered fuels quality and air pollution. Highlights: Ranking of negative cost options is unreliable in marginal abatement cost curves. This study employed extended versions of marginal abatement cost curves. We empirically demonstrate the bias in marginal abatement cost curves. Our method explicitly addresses the problem of ranking negative cost options.